Differences in perception of burnout syndrome among young athletes from individual and team sports - Santos,Ana Clécia Alves dos (2020)
The purpose of this study was to compare the perception of the burnout syndrome related to the variables gender, sport, and age in young swimmers and volleyball players. A total of 194 athletes of both genders, aged 14 to 17 years, completed the Athlete Burnout Questionnaire (ABQ). The data analysis consisted of descriptive statistics and a comparison of the studied variables using the Kruskal-Wallis and Mann-Whitney tests. The results showed that the athletes did not have high burnout syndrome indicators. We found no effect of the gender variable on the perception of burnout dimensions. Swimmers had greater physical and emotional exhaustion than their volleyball peers. Conversely, volleyball players perceived more sport devaluation than their swimming peers.